Efeito da adição de boro na microestrutura e na resistência ao desgaste do aço inoxidável AISI 430 conformado por spray - Nascimento, Alexandre Romão Costa (Universidade Federal de São Carlos, 2014)
The contact between drill pipes during oil well exploitations induces a severe wear process that might cause well bore pipe wall rupture, fluids leakage, environmental impacts, and possibly fatal accidents. The problem is known by the oil and gas industries since the 1930 s and several solutions have been proposed by researchers and engineers in order to mitigate its deleterious effects. A method that grows popular in the industrial media is the execution of large-scale tests that consists in forcing a cylinder against the inner wall of a pipe. During this test, in order to reproduce operations conditions, the use of drilling mud as a lubricant and a wear resistant coating over the cylinder are both possible. The purpose of this work was to evaluate the effect of boron addition on the microstructure of spray-formed AISI 430 stainless steel as well as in its wear resistance in a condition comparable to the one observed during drill pipes contact. It was then necessary to develop a wear tester capable of reproducing the changes in the contact areathat occurs during the aforementioned contact. The results showed that unlike the conventional API 5L X80 steel, the spray-formed material s wear rates were constant as predicted by Archard s wear law. Despite the different wear rate behaviors, the generated wear debris showed a similar morphology in all tested materials. The tribossystem conditions induced a plastic ratchetting wear mechanism. In the light of Greenwood and Williamson s theoretical model, it was concluded that the observed changes in the wear rate on conventional steels was due to slow changes in the plasticity index which happens much more quickly in the sprayformed steels due to the presence of intermetallic borides. Moreover, considering the established test parameters, the increase in the boron content also increases the AISI 430 steel s wear resistance, since the increase in the area fraction of intermetallics decreases the rate at which metallic asperities contact each other during the test.
effect of boron addition on the microstructure and wear resistance of a spray-formed AISI 430 stainless steel
Keywords: Aço inoxidável; Resistência ao desgaste; Tubos de perfuração; Conformação por spray; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA